Thermo-responsive surfaces for enzyme free mammalian cell culture - Dey, Sabrina (2010)
Embryonic stem cells are of great interest to scientists as they can differentiate into any somatic cell lineage making them excellent candidates for tissue regeneration and cell based treatment therapies. Currently, human embryonic stem cells (hESCs) are cultured using feeder fibroblasts or protein substrates such as matrigel, fibronectin or laminin in conditioned media. hESCs are then subcultured using enzymes to detach them from the culture substrate. However, the use of the xenosupport systems makes the hESCs therapeutic applications difficult due to cross-contamination with animal pathogens from the animal derived feeders, matrix or conditioned media to the hESCs. Moreover, the use of enzymes to recover hESCs can damage these cells. For the mentioned reasons, development of completely synthetic surfaces is desirable for hESCs culture. Thermo-responsive surfaces have been extensively studied for cell culture using the well know thermo-responsive polymer poly (N-isopropylacrylamide) (PNIPAAM) which has a switchable properties across its lower critical solution temperature (LCST) at 32°C. However, more biocompatible polymers that have similar thermo-responsive properties to PNIPAAM and biocompatible properties, such as PEG based materials, have been proposed for use as switchable surfaces. Within this thesis, thermo-responsive copolymer brushes composed of 2-(2- methoxyethoxy) ethylmethacrylate (ME02MA) and oligo (ethylene glycol) methacrylate (OEGMA) that have LCST close to body temperature (37°C) were investigated for use as a cell culture surface for temperature sensitive passaging. Poly (ME02MA-co-OEGMA) brushes were grafted from the surface using atom transfer radical polymerisation (ATRP). Hydroxyl plasma-polymer functionalised glass slides were prepared using plasma polymerisation and then an ATRP initiator was reacted to these surfaces. ATRP of the copolymers was then performed from these initiation sites. These surfaces were characterised using X-ray photoelectron spectroscopy (XPS), Time of Flight Secondary Ion Mass Spectroscopy (ToF-SIMS), atomic force microscopy (AFM) and water contact angle (WCA). Using 3T3 fibroblasts as a model cell type for initial studies, it was demonstrated that these cells adhered and proliferated on the poly (ME02MA-co-OEGMA) thermo-responsive surfaces at 37°C when the polymer brushes are in their hydrophobic state. Subsequent detachment assays were conducted when the temperature was lowered to 20°C i.e. the hydrated conformation of the copolymer brushes. Mouse embryonic stem cells (mESCs) were then cultured on these surfaces following adsorption of fibronectin (to encourage cell attachment) and cultured for 3 days. Passaging experiments were performed for 10 passage cycles and the cells analysed for retention of the undifferentiated stem cell status. These thermoresponsive polymer/fibronectin surfaces are found to be suitable for mESCs culture but evidence of differentiation was observed. Attachment of a novel gelatine based peptide to the poly (ME02MA-co-OEGMA) was also investigated for mESCs culture to avoid the use of fibronectin (which was thought to be a contributing factor to the stem cell differentiation seen). mESCs adhesion was observed both to the peptide adsorbed on TCPS and on the peptide coupled to the thermo-responsive poly (ME02MA-co-OEGMA) surface. This research indicates that these smart stimuli biomaterials have promise as a new generation of culture surfaces for enzyme free cell culture and passage suitable for generating cell populations for clinical applications.